Compatibilization strategies and analysis of morphological features of poly(butylene adipate-co-terephthalate) (PBAT)/poly(lactic acid) PLA blends: A state-of-art review - Aversa, C.; Barletta, M.; Cappiello, G.; Gisario, A. (European polymer journal, 2022)
[Display omitted] •PBAT is of great interest among bioplastics potentially obtainable from renewable resources.•PBAT occupies 19.2% of the bioplastics market share, competing with PLA (18.9% market share)•PBAT is blended with PLA, a rigid bio-based polymer, to design multi-functional biodegradable plastics.•Summarize the design criteria used in engineered plastics based on PBAT/PLA blends.•Develop a useful guide to promote the use of biodegradable materials instead of conventional plastics. PBAT is a compostable biopolyester, potentially obtainable from renewable resources, of great commercial interest. Thanks to its lower price, ease in processability and especially high ductility PBAT will very likely emerge in the next few years as the preeminent flexible bioplastic, ahead of contenders such as polybutylene succinate (PBS) or polycaprolactone (PCL) and it will likely become one of the most important biodegradable plastics, alongside PLA, which stays the major biopolymer for rigid applications. PBAT is often blended with PLA, a rigid bio-based polymer, that lends stiffness. PLA is a very rigid material with low impact resistance, it is, therefore, complementary to PBAT in the design of high performance and multi-functional biodegradable plastics. Despite the great and increasing interest of the market in PBAT, to date a general overview of the scientific literature which critically explores potentials of PBAT, with focus on design of engineered PBAT/PLA blends, is missing. The present works aims at filling this gap, laying the basis to create a link between fundamental research on PBAT and industrial applications. A general overview of the market and of the state of the art of PBAT based blends is herein provided, focusing on PBAT/PLA blends and possible compatibilization strategies. This work aims to achieve a double target: scientific and social. The scientific target is to summarize the main design criteria used in the conception of engineered plastics based on PBAT blends with PLA, revealing their implementation secrets and strategic aspects. The social target is to develop a useful guide for sector technicians, policy makers and stakeholders to promote the use of biodegradable materials instead of conventional plastics in an even wider range of applications, in order to significantly reduce the environmental impact of plastic products.